(3TQM CdajI GHf eGdc aj GdfMhs - (3GdbQTj GdgGTej, GHf Ybjd (B, (3CHh eMeO, HgGA GdOjf, YHO Gddg Hf YHO GdQMef Hf YHO Gddg Hf eMeO, (B769 (3g`s
(3ChdgG (B:s
(3bGd eMeO gh GHf eGdc (B*** (3CMeO QHj Gddg NjQ eGdcs
(3BNQgG (B:s
(3aCMeO Gddg eUdjG Ydi (B*** (3eMeO NjQ fHj CQSdG , hBdg GdYR GdcQGe GdHQQI (B*** (3hUMHg GdefJNHjf GdNjQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 96s
(3eYLe GdeDdajf(B: 2 / 251s
(3cTa GdXfhf(B: 1 / 152s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs